Edukasi 10 Pesan Gizi Seimbang dengan Penerapan "Isi Piringku" pada Siswa Sekolah Dasar Negeri Locare 1 - Prakoso, Bhim; Qori’ah, Ciplis Gema; Wardhono, Adhitya; Nasir, M Abd; Puspito, Agung Nugroho; M, Akmal Iqbal; Y, Erwina Dwi; Z, Najmah Tsuraya; F, Sandrina Naura; A, Sefia Aura; R, Shofiatur; Permata, Dini (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
There is still a widespread lack of control over their diet, which can negatively impact their health. Most people, especially children, ignore the consequences and are primarily driven by hunger and curiosity about food. They are more attracted to food when they find something they find unique and different. Nowadays, more and more foods are being mixed with colorings, preservatives, and flavorings, which makes children want to continue consuming them. Consuming them too often can be detrimental to their health both now and in the future. Lack of knowledge about healthy eating for children and their parents leads them to neglect the food they eat. As time progresses, food types become more diverse, such as the increasing availability of fast food and instant foods, which are easily accessible but have negative health impacts. In this journal, we took samples from elementary school students. The purpose of this journal is to introduce children, especially elementary school students, to implementing a balanced diet through the concept of "fill my plate." The method used is by delivering material in elementary school and asking questions to gauge their understanding of the material presented. The results of the activities carried out showed that many elementary school students still lack knowledge about the types of healthy foods and healthy eating patterns for the body. It can be concluded that many elementary school students still lack understanding about healthy food, due to limited access, both from their families and their economic conditions, which are inadequate to find nutritious food. Social projects related to balanced nutrition are very urgent and important as an effort to support government programs related to the health and welfare of the Indonesian people.